Investigation of Kidney Stone Using a Microstrip Patch Antenna Scanning System - ALWAN, Mohamad; SADEK, Sawsan (Journal of Diagnostics, 2016)
The abnormalities of the kidney can be identified by ultrasound imaging. The kidney may have structural abnormalities like kidney swelling, or change in its position and appearance. Kidney abnormality may also arise due to the formation of stones, congenital anomalies, blockage of urine etc. For surgical operations it is very important to identify the exact and accurate location of stone in the kidney. The ultrasound images are of low contrast and contain speckle noise and could affect human body in some situations like pregnancy. This makes the detection of kidney abnormalities rather challenging task. Thus, microwave imaging could be a good alternative. A microstrip patch antenna scanning system allows to identify the exact and accurate location of stone in the kidney. A physical testing system will be developed in order to generate antenna response surfaces on material which could represent the human body. The serum is used in the experimental measurement because it has similar dielectric properties as human body. In order to represent stone presence in an homogenous medium, small calcium sto ne bearings of different sizes embedded are used to simulate the abnormality. Compact microstrip patch antenna were designed and tested at different frequencies in ISM band : 2.26 GHz, 2.38 GHz, 2.5 GHz, and 2.62 GHz for the RF investigation imaging system in order to detect and localize stones in the kidney.